Building Human Capital : Lessons from Country Experiences – Philippines - King, Elizabeth (World Bank, Washington, DC, 2020)
Human capital is the Philippines’ most important resource. Two examples of its benefit to the country: remittances from skilled and semi-skilled workers who work abroad amount to about 10 percent of its GDP, and it is one of the top destinations for foreign enterprises seeking educated workers for outsourcing their business processes. However, the Philippines has been losing its human capital edge over the past decades, with critical gaps in access to social services and in the quality of those services. In 2018, its rating on the Human Capital Index, a composite measure based on survival rates, the quantity and quality of schooling, and health status, was 0.55, putting it just ahead of Indonesia but well below Malaysia, Thailand, and Vietnam. Within the past decade, the Philippines adopted an ambitious national social agenda that, if implemented well, funded adequately, and monitored assiduously, could put it back on a more robust human development path. All efforts should be made, however, to safeguard this promising agenda from the implementation problems that evidence suggests have subverted the country’s past performance, weak governance, selfish political interest, and widespread corruption. Sound policies won’t lead to progress unless they are implemented well across the agencies and levels of government.